Pengaruh Pelayanan dan Asosiasi Merek terhadap Kepercayaan Pelanggan Bengkel Kendaraan Bermotor dan Dampaknya terhadap Preferensi Rekomendasi - Nasir, Muhadjir; Rachmawati, Febri (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
The number of motorcycles being sold in Indonesia keeps increasing every year. Every manufacturer should stand firm on negotiating to what extent service and brand name impact to consumer trust and recommendation preference.Â  This research aims to investigate this issue using path analysis. Sample is taken from community of car garage consumers. Then, data is verified by some statistical tools such as normality, validity and reliability before using path analysis. The research findings confirm that service quality, brand association and consumer trust are very important to attract trust over garage service. Concerning this issue, the researcher contributes some suggestions such as management should increase service quality by doing employee professionalism improvement. For doing this, the firm can exploit on employee training; implementing incentive strategy to motivate employees, exposing openness and positive atmosphere to interact with consumers and the last but not the least, to maintain good relationship for short and long term by providing consumers with a forum-based communication media.